STATE SOIL MAP AND ITS CREATORS - D. Ye. Konyushkov; S. F. Khokhlov; A. A. Kontoboitseva; N. V. Savitskaya (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
The State Soil Map (SSM) on a scale of 1 : 1 M is the greatest product of Russian small-scale soil cartography that accumulates data on soils of the Former Soviet Union for the entire period of the development of Dokuchaev's pedology. The work on the SSM was initiated by L.I. Prasolov in the 1930s; the official history of the SSM dates back to the governmental decree of 1946. For nearly 40 years, the works on the SSM were headed by I.P. Gerasimov. The huge amount of research was performed under the guidance of E.N. Ivanova. The compilation of the SSM gave strong impetus to the development of genetic pedology and geography of soils. It clearly demonstrated "blank spots" in our knowledge of soils, where special field studies were organized. The main stages of the development of the SSM are discussed, and the specific features of its program for the northern and Siberian territories are elucidated. More than a thousand specialists in the geography and cartography of soils contributed to this map. A special database on the SSM was developed. It contains detailed information on the published map sheets, their authors, cartographers, and editors; it also contains information about the authors of factual materials used during the compilation of the map. The major cartographic features of the design of the map are discussed. The modern state of the work on the SSM is briefly characterized, and the problems related to its publication and practical use are considered. As a positive example of the desirable future of the SSM, information on the current status and progress of the work on the "elder sister" of the SSM-the State Geological Map on the same scale (1 : 1 M)-is given. The main aim of this paper is to attract attention to the SSM as the most significant and, unfortunately, underestimated source of information on soil resources.